Rejuvenation by weakening the medium range order in Zr46Cu46Al8 metallic glass with pressure preloading: A molecular dynamics simulation study. (15th November 2018) - Feng, S.D.; Chan, K.C.; Zhao, L.; Pan, S.P.; Qi, L.; Wang, L.M.; Liu, R.P.
Abstract: Rejuvenation is the structural excitation of metallic glasses that can significantly increase the enthalpy and free volume. Here, the rejuvenation in Zr46 Cu46 Al8 metallic glasses with pressure preloading was studied by molecular dynamics simulation. As the strain gradually increases, high-density deformation units in different regions are formed in the rejuvenated Zr46 Cu46 Al8 metallic glass with pressure preloading, but they do not form the shear bands that cause brittle fracture. In terms of the microstructure, the pressure preloading increases the degree of the short range order, but decreases the medium range order. 3-atom connections in the medium range order of icosahedra and other clusters are proposed to represent the level of rejuvenation. The decrease of 3-atom connections in the medium range order can lower the energy barrier and decrease the elastic modulus, improving the level of the rejuvenation. With the weakening of the 3-atom connections, the rejuvenated metallic glass possesses the features of high density, high energy, high Poisson's ratio, high defects and low localization. These findings open an avenue to evaluate the level of rejuvenation and provide a strong foundation for metallic glass design. Graphical abstract: Highlights: The pressure preloading increases the short range order, but decreases the medium range order in Zr46 Cu46 Al8 metallic glass. The decrease of 3-atom connections in the medium range order improves the level of rejuvenation. 2-atom and 4-atom connections in the medium range order lead to more local plastic units being activated.